Self-protected nitrate reducing culture for intrinsic repair of concrete cracks - Erşan, Yusuf Ç.; Gruyaert, Elke; Louis, Ghislain; Lors, Christine; De Belie, Nele; Boon, Nico (Frontiers in Microbiology, 2015)
Attentive monitoring and regular repair of concrete cracks are necessary to avoid further durability problems. As an alternative to current maintenance methods, intrinsic repair systems which enable self-healing of cracks have been investigated. Exploiting microbial induced CaCO3 precipitation using (protected) axenic cultures is one of the proposed methods. Yet, only a few of the suggested healing agents were economically feasible for in situ application. This study presents a NO3- reducing self-protected enrichment culture as a self-healing additive for concrete. Concrete admixtures Ca(NO3)2 and Ca(HCOO)2 were used as nutrients. The enrichment culture, grown as granules (0.5 – 2 mm) consisting of 70 % biomass and 30 % inorganic salts were added into mortar without any additional protection. Upon 28 days curing, mortar specimens were subjected to direct tensile load and multiple cracks (0.1 – 0.6 mm) were achieved. Cracked specimens were immersed in water for 28 days and effective crack closure up to 0.5 mm crack width was achieved through calcite precipitation. Microbial activity during crack healing was monitored through weekly NOx analysis which revealed that 92±2 % of the available NO3- was consumed. Another set of specimens were cracked after 6 months curing, thus the effect of curing time on healing efficiency was investigated, and mineral formation at the inner crack surfaces was observed, resulting in 70 % less capillary water absorption compared to healed control specimens. In conclusion, enriched mixed denitrifying cultures structured in self-protecting granules are very promising strategies to enhance microbial self-healing.